Immunologic impact of chemoradiation in cervical cancer and how immune cell infiltration could lead toward personalized treatment. Issue 2 (26th February 2020) - Lippens, Lien; Van Bockstal, Mieke; De Jaeghere, Emiel A.; Tummers, Philippe; Makar, Amin; De Geyter, Sofie; Van de Vijver, Koen; Hendrix, An; Vandecasteele, Katrien; Denys, Hannelore
Abstract : We investigated the potential of tumor‐infiltrating immune cells (ICs) as predictive or prognostic biomarkers for cervical cancer patients. In total, 38 patients treated with (chemo)radiotherapy and subsequent surgery were included in the current study. This unique treatment schedule makes it possible to analyze IC markers in pretreatment and posttreatment tissue specimens and their changes during treatment. IC markers for T cells (CD3, CD4, CD8 and FoxP3), macrophages (CD68 and CD163) and B cells (CD20), as well as IL33 and PD‐L1, were retrospectively analyzed via immunohistochemistry. Patients were grouped in the low score or high score group based on the amount of positive cells on immunohistochemistry. Correlations to pathological complete response (pCR), cause‐specific survival (CSS) and metastasis development during follow‐up were evaluated. In analysis of pretreatment biopsies, significantly more pCR was seen for patients with CD8 = CD3, CD8 ≥ CD4, positive IL33 tumor cell (TC) scores, IL33 IC < TC and PD‐L1 TC ≥5%. Besides patients with high CD8 scores, also patients with CD8 ≥ CD4, CD163 ≥ CD68 or PD‐L1 IC ≥5% had better CSS. In the analysis of posttreatment specimens, less pCR was observed for patients with high CD8 or CD163 scores. Patients with decreasing CD8 or CD163 scores between pretreatment and posttreatment samples showed more pCR, whereas those with increasing CD8 or decreasing IL33 IC scores showed a worse CSS. Meanwhile, patients with an increasing CD3 score or stable/increasing PD‐L1 IC score showed more metastasis during follow‐up. In this way, the intratumoral IC landscape is a promising tool for prediction of outcome and response to (chemo)radiotherapy. Abstract : What's new? This study explored the effects of (chemo)radiotherapy on the tumor immunome and the potential of tumor‐infiltrating immune cells as predictive or prognostic biomarkers in a unique cervical cancer population treated with (chemo)radiotherapy and subsequent surgery. Analysis of pre‐ and post‐treatment immune cell markers, and their changes during treatment showed correlations with pathological response, survival, and metastasis. The CD8/CD3 ratio, CD8/CD4 ratio, IL33‐tumor cells, IL33‐immune cell/tumor cell ratio, and PD‐L1‐tumor cells may predict pathological complete response and thus radiosensitivity in cervical cancer. Investigation of these markers in future trials may thus lead to more personalized care for cervical cancer patients.